2008
DOI: 10.2174/1874315301002010087
|View full text |Cite
|
Sign up to set email alerts
|

The Possible Protective Role of the Il6-174GC Genotype in Dengue Fever

Abstract: Dengue is the most important viral disease transmitted by arthropod vectors. At present, it is known four types of virus serotypes, DEN 1, 2, 3 and 4. Differences in the host susceptibility to infection as well as the severity of disease can not be due only to viral virulence. Variations in immune response as a consequence of polymorphisms in regulatory regions of cytokine genes may have influence on the disease outcome. The aim of this study was to verify the occurrence of associations between cytokine gene p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Correlation between TNF-α -308A allele and DHF has been reported earlier in patient population of Venezuela and Cuba 38 , 39 , but other studies did not find association in their group of patients 40 - 43 . A study in Mexico showed that the -238A allele was associated with protection of symptomatic dengue 41 .…”
Section: Discussionmentioning
confidence: 59%
“…Correlation between TNF-α -308A allele and DHF has been reported earlier in patient population of Venezuela and Cuba 38 , 39 , but other studies did not find association in their group of patients 40 - 43 . A study in Mexico showed that the -238A allele was associated with protection of symptomatic dengue 41 .…”
Section: Discussionmentioning
confidence: 59%
“…Some of these polymorphisms influence the level of cytokine production, which can confer flexibility in the immune response [98101]. Thus, the presence of certain alleles may influence the course of bacterial and viral infections [102, 103] and confer susceptibility or resistance to autoimmune disease [104]. SNPs in cytokine genes have been described as important genetic factors in the occurrence of different clinical forms of Chagas disease.…”
Section: Genetic Factors and Their Influence On Chagas Diseasementioning
confidence: 99%